Adjustment of the leg spring for stable running - Seyfarth, A.; Geyer, H.; Günther, M.; Blickhan, R.
A simulation study is presented to investigate the adjustment of leg stiffness and touch-down angle of attack during running. The centre of mass trajectory was described in terms of a planar spring-mass system during the stance phase and a ballistic flight phase. We found that for certain angles of attack the system becomes self-stabilised if a minimum running speed was exceeded. Furthermore, the leg stiffness had to be adjusted to the chosen angle of attack. Different running techniques fulfilling a stable movement pattern are possible. The mechanical stability of the system was shown by an one-dimensional return map of the landing velocity angle. With elastically operating legs the techniques predicted for stable running are in agreement with experimental studies. The objective of running is simply to gain periodic movement patterns.